Induction of IFN-α Subtypes and Their Antiviral Activity in Mumps Virus Infection - Markušić, Maja (Viral Immunol, 2014)
Human type I interferons (IFNs) comprise one IFN-β, -ω, -κ, and -ɛ and 12 different IFN-α subtypes, which play an important role in early host antiviral response. Despite their high structural homology and signaling through the same receptor, IFN-α subtypes exhibit different antiviral, antiproliferative, and immunomodulatory activities. Differences in the production of IFN-α subtypes therefore determine the quality of an antiviral response. In this study, we investigated the pattern of IFN-α subtypes induced in infection with different mumps virus (MuV) strains and examined the MuV sensitivity to the action of IFN-α subtypes. We found that all IFN-α subtypes are being expressed in response to MuV infection with a highly similar IFN-α subtype pattern between the virus strains. We assessed an antiviral activity of several IFN-α subtypes: IFN-α1, IFN-α2, IFN-α4, IFN-α6, IFN-α8, IFN-α14, IFN-α17, and IFN-α21. Although they were all effective in suppressing MuV replication, the intensity and pattern of their action varied between MuV strains. Our results indicate that the overall IFN antiviral activity as well as the activity of specific IFN-α subtypes against MuV depend on a virus strain.